Interaction of a water soluble fullerene derivative with reactive oxygen species and model enzymatic systems - Foley, Sarah; Curtis, Anthony; Brettreich, Michael; Hirsch, Andreas; Pelegrin, Andre; Seta, Patrick; Larroque, Christian (Fullerenes Nanotubes and Carbon Nanostructures, 2002)
Fullerenes are a new class of compounds with potential uses in biology and medicine but little is known about their interaction with biological systems. Fullerenes were reported to be pro- or anti-oxidants depending on their structure or on experimental conditions. This work presents the effects of dendrofullerene, a water soluble derivative of C , on model biological systems from both perspectives. The relative importance of type I and type II mechanisms involved in the production of the reactive forms of oxygen leading to inhibition of GST activity was studied using dendrofullerene, white light and the quenching agents. The addition of mannitol or superoxide dismutase, known quenchers of the type I mechanism had no effect on the rate of GST inactivation. Significant inhibition of the inactivation provided by the dendrofullerene was observed on addition of tryptophan, a known quencher of the type II mechanism. Activity towards the basic enzymatic system cytochrome P-450 has also been investigated and at a concentration of 250 μM dendrofullerene exhibits selective inhibition of progesterone metabolism which is attributed to the fullerene moiety rather than the dendritic chain.